1998
DOI: 10.1021/tx970185w
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Serotonin by Superoxide Radical:  Implications to Neurodegenerative Brain Disorders

Abstract: Many new lines of evidence implicate both superoxide anion radical (O2*-) and biogenic amine neurotransmitters in the pathological mechanisms that underlie neuronal damage caused by methamphetamine (MA), glutamate-mediated oxidative toxicity, ischemia-reperfusion, and other neurodegenerative brain disorders. In this investigation the oxidation of 5-hydroxytryptamine (5-HT, serotonin) by an O2*--generating system (xanthine/xanthine oxidase) in buffered aqueous solution at pH 7.4 has been studied. The major prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
111
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 61 publications
0
111
1
Order By: Relevance
“…Normally, excess 5-HT is enzymatically converted to compounds such as 5-HIAA, one of several stable oxidized forms of indoleamine. Under conditions of oxidative stress, polymerized products of indoleamine oxidation can form and have been implicated in the etiology of neurodegenerative diseases such as AD, several psychotic diseases, and the neurodegenerative effects of amphetamines (37). The primary aberrant oxidation products of 5-HT, such as tryptamine diones, undergo rapid dimerization resulting in fluorescent compounds colocalized with the monoamine pool.…”
Section: Resultsmentioning
confidence: 99%
“…Normally, excess 5-HT is enzymatically converted to compounds such as 5-HIAA, one of several stable oxidized forms of indoleamine. Under conditions of oxidative stress, polymerized products of indoleamine oxidation can form and have been implicated in the etiology of neurodegenerative diseases such as AD, several psychotic diseases, and the neurodegenerative effects of amphetamines (37). The primary aberrant oxidation products of 5-HT, such as tryptamine diones, undergo rapid dimerization resulting in fluorescent compounds colocalized with the monoamine pool.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Dryhurst and coworkers (Jiang et al 1999;Wrona and Dryhurst 1998) have identified a number of toxic 5-HT metabolites, in addition to 5,6-DHT, but the in vivo synthesis of these metabolites has not been demonstrated. Because no studies have assessed the formation of toxic 5-HT metabolites after injection of FEN or dFEN, this issue remains unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Excesses of superoxide anion in the human body are kept in check by an antioxidant enzyme system including SOD, GPX, and catalase (Cat). Superoxide anion has been reported to cause nerve degeneration 12) and heart failure. 13) SOD activity in blood sample from patients with thyroiditis, dwarfism, and Turner syndrome has been found to be lower than in healthy persons.…”
mentioning
confidence: 99%